Investigating the Impact of Elevated Government Debt on Economic Growth in Developing Nations - Mehaluddin Siddiqui; Syed Zia Abbas Rizvi; Khurram Iftikhar; Muhammad Imran Khan (Al-Qanṭara, 2024)
This study aims to empirically investigate the impact of borrowing on the GDP of developing economies after the financial crisis. Additionally, it aims to examine the significance of the investment channel of national debt in affecting economic growth. Another objective is to analyze the impact of debt on total investment. This study also assesses the influence of macroeconomic factors such as Gross Fixed Capital Formation (GFCF), government debt, bond yields, foreign trade balance, government revenues, and GDP on the growth of developing countries. The research is based on panel data from 99 countries (classified as developing countries by the World Bank) spanning from 2000 to 2020, covering periods before and after financial crises. The Generalized Method of Moments (GMM) technique is employed for estimation purposes. The first model revealed a negative relationship between government debt and GDP, indicating that a percentage change in government debt is associated with a decrease in economic growth. This finding suggests that high levels of government debt may impede economic expansion, potentially due to crowding-out effects on private investment and increased fiscal vulnerabilities. The second model presented a contrasting result, indicating a positive relationship between government debt and investment (Gross Fixed Capital Formation, GFCF) in specific circumstances. It suggests that, under certain conditions, government borrowing may stimulate investment activities and infrastructure development, potentially contributing to economic growth. The analysis highlighted temporal dynamics in investor behavior before and after financial crises. It suggests that the relationship between government debt and investment may vary over time, influenced by economic conditions and external shocks. Understanding these temporal dynamics is crucial for formulating effective policy responses and managing fiscal policy in developing economies. The findings of the present study validate the conclusions drawn from previous research in developing countries, highlighting the adverse effects of government debt on economic growth. By better understanding the implications of high debt levels, policymakers can formulate strategies to manage debt effectively and promote sustainable economic development. Top of Form